Analysis of cutaneous adverse drug reactions reported at the regional ADR monitoring center - Anal Modi; Mira Desai; Samidh Shah; Bela Shah (Wolters Kluwer Medknow Publications, 2019)
Introduction: Skin is one of the major target organ for adverse drug reactions (ADRs). The incidence of dermatological ADRs among indoor patients in developed countries ranges from 1-3%, whereas in developing countries such as India, it is 2-5%. Aims: To analyze the clinical spectrum, seriousness, outcome, causality, severity, and preventability of the cutaneous ADRs. Material and Methods: All cutaneous ADRs reported at the Regional Adverse Drug Reaction Monitoring Center between January 2013 to May 2016 were identified and evaluated. A retrospective analysis was carried out for clinical presentation, causality (as per the WHO-UMC scale and the Naranjo'a reactions (ADRs) Severity (Hartwig and Seigel scale), and preventability (Schumock and Thornton criteria) of a said drug. Results: Out of 2171 ADRs reported during study period, 538 were cutaneous ADRs (24.78%). The most common clinical presentation was maculopapular rash (58.92%) followed by itching (10.59%), and Stevens-Johnson syndrome (4.83%). The time relationship of cutaneous ADRs to drug therapy revealed that they can develop within 1 week to 1 year of treatment. Most common causal drug groups were antimicrobials (46%), non-steroidal anti-inflammatory drugs (NSAIDs) (18%), and antiepileptics (10%). Polypharmacy was observed in 7% of the cases. Most of the cutaneous ADRs were non-serious (91%), however, 10 were life-threatening and 1 was resulted in death due to the Stevens-Johnson syndrome. Causality category for majority of cutaneous ADRs was possible. Although majority of cutaneous ADRs were moderately severe (81%), however, not preventable (89%). Conclusion: The occurrence of cutaneous ADRs is common and they developed within 1 week of therapy. Antimicrobial agents and NSAIDs are the most common implicated drug class. Hence, physicians should closely monitor the patient in the first week while using such therapy for early detection and prevention of cutaneous ADRs.